HUBUNGAN BEBERAPA FAKTOR DENGAN KEJADIAN UNMET NEED KELUARGA BERENCANA DI KELURAHAN BULU LOR - Dewi, Fadyan Ratna; Winarni, Sri; Nugroho, Djoko (Jurnal Kesehatan Masyarakat (e-Journal), 2018)
Unmet need of family planning is a reproductive age couples that did not use contraception, however they want delay pregnancy (for spacing) or even stop giving child birth (for limiting). The prevalence of unmet need on Bulu Lor was quite high (15.9%). The aim of this study was to analyze the relationship of several factors towards to incidence of unmet need for family planning. The research method used in this study was explanatory research using cross sectional study approach. Population in this study were 1,869 with 95 sample from  women in reproductive age, who were chosen by simple random sampling technique. There were three analyses used in this study; univariate analysis, bivariate, analytic (chi square test). The result of univariate analysis showed that 60% wife has well knowledge, 56.8% wife has supportive attitude, 57.9% gets husband’s support, and 41.1% has incidence of unmet need for family planning with unmet need for spacing (11.6%) and unmet need for limiting (29.5%). The result of bivariate analysis showed that unmed need of family planning occurred in wife with poor knowledge (44.7%),  wife with less supportive attitude (48.8%), and did not get support form husband (67.5%). Chi square test with continuity correction method revealed that there was a significant relationship among husband’s support with incidence of unmet need for family planning (= 0.001; 95% CI = 2.965 to 18.683), and there was not significant relationship among wife’s knowledge (=  0.702; 95% CI = 0.560 to 2.961) and wife’s attitude (= 0.261; 95% CI = 0.766 to 4.019). This study encourages other researcher to have further research about it. This study also suggests to promotion of family planning.